Composition analysis of writing materials in Cairo Genizah documents - Cohen, Zina (Cambridge Genizah studies series ;, 2021)
"Through the application of scientific methods of analysis to a corpus of medieval manuscripts found in the Cairo Genizah, this work aims to gain a better understanding of the writing materials used by Jewish communities at that time, shedding new light not only on the production of manuscripts in the Middle Ages, but also on the life of those Jewish communities"--